Korupsi dalam Pembangunan Wilayah: Suatu Kajian Ekonomi Politik dan Budaya - Riyanto, Riyanto; Gonarsyah, Isang; Fauzi, Akhmad; Dharmawan, Arya Hadi (Jurnal Ekonomi dan Pembangunan Indonesia, 2008)
The main objective of the study is to analyze the political economic and cultural factors affecting corruption in regional economic development during decentralization era in Indonesia. The research uses both qualitative and quantitative methodology to elaborate the process of policy making in budgeting and in formulating regional regulation (Perda). Three districts were chosen as case studies i.e. Kabupaten Solok, Kabupaten Sukoharjo and Kabupaten Kutai Kartanegara. The results of the study indicate that corruption has already emerged since the begining of decision making process in the executive as well as legislative agencies. The findings show that political economic and cultural factors are strongly affecting the corruption in regional development in the autonomy era.